Los inmigrantes de Saint Kitts: 1910, un capítulo en la historia de los conflictos bananeros costarricenses - Hernández, Carlos (1990)
In this article, the author seeks to reconstruct and explain a revolt by United Fruit Company workers in 1910. He assesses the organizational level attained by the workers, the nature of the labor-capital conflict, and the attitude of the State vis-à-vis events of the time.